Education for the value of rule of law in the European Union - Silva, Maria Manuela Magalhães (2022)
The effective exercise of democracy implies informed citizens as a result of an education policy that forms awareness of fundamental rights, through the idea of the rule of law and, most recently, knowledge about the European Union. To this end, new digital technologies can be an excellent instrument in order to achieve that outcome. Within the European Union, in addition to its countries, as in the world, the rule of law emerges as a value enshrined in the constitutional texts. A concept that was born from the advent of constitutionalism and is not easy to describe. However, essential to the way of life we know, since respect for the rule of law is a condition for guaranteeing democracy and fundamental rights. It is not even stated in the Portuguese Constitution or in the founding treaties of the European Union. But the EU has a role to play in resolving issues related to the rule of law because respect for the rule of law is a precondition for upholding all rights and obligations arising from the Treaties and secondary legislation. The idea must be disseminated to all citizens and digital media are useful for this purpose. And if this is less obvious for jurists, is the value it contains effectively communicated to the citizens who benefit from it? Does education convey the explanation of what respect for the rule of law really means for the life of each citizen? And how to find the link to promote their understanding through education? How to use digital media to increase dissemination? The questions are multiple and it is important for us to bring them to the debate in order to reach an answer or at least an approach. It is true that the doctrine has densified the concept. The soft law documents of the European Union institutions contribute a lot. At a time when some European Union countries are alerted to of this constitutional achievement being in danger, even resulting in an example of pecuniary sanctions, it is also from the jurisprudence of the Court of Justice of the European Union (CJEU) that the simplest explanations come to us. The CJEU was a pioneer in clarifying the concepts used by European Union law since the first years of activity and still maintains this role today. The purpose of this analysis is to demonstrate that, as Member States are primarily responsible for the application of EU law, there is still an effort to be made for the efficiency of citizens' understanding of the rule of law, as a value of the European Union. Emphasize the importance of including in (digital) education the concept of the rule of law and the consequences of disrespecting it for the lives of citizens and their rights. Considering the embryonic nature of this study, a methodology was designed that focus on the use of European Union law sources, through systematic and methodologically selected normative interpretation. It focuses on specialized publications but above all official documents (legislative or preparatory) and jurisprudence that set out the issue. The theoretical-academic tendency is consolidated through systematic normative interpretation and aims to expand knowledge, in a qualitative and exploratory approach. Without presenting quantitative data, the purpose is to bring to discussion and debate the value os the rule of law in the context of the European.